Movement patterns of the spiny lobster Palinurus elephas (Fabricius, 1787) from a central western Mediterranean protected area - Follesa, Maria Cristina; Cuccu, Danila; Cannas, Rita; Sabatini, Andrea; Deiana, Anna Maria; Cau, Angelo (Scientia Marina, 2009)
Movement patterns of the spiny lobster Palinurus elephas were determined from 389 individuals (total tagged 5666) tag-recaptured inside a no-take area of the central western Mediterranean and its surrounding zone. High site association and limited movements in tagged lobsters was observed; 60.4% of lobsters moved less than 2 km from the centre of the area (site of release). No clear relationship between lobster movement pattern and sex or size was observed; however, it seemed that the largest males and females tended to be more resident, thus contributing to the rebuilding of the biomass of local lobsters. Most lobsters undertook migrations in the southwest direction. The increased availability of shelters and food towards the southwest could have contributed to the lobsters’ movement. The results of our research indicate that the small size of the protected area and the scale of the movement exhibited by tagged lobsters allows a proportion of the lobster population to move out of the protected area and become susceptible to capture in the adjacent fishery.